Emotional response and its relationship to the level of performance skills the fronting transmission from up and hitting the ball to the skill spike Front of the volleyball. (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the relationship between the emotional response and the performance of the two skills of serving from above (the tennis serve) and the crushing blow in volleyball.The researcher used the descriptive method (in the relational method) because it is appropriate to the nature of the problem.The research sample included (9) players from the Akadankawah Sports Club for volleyball applicants, who were chosen by the intentional method. The emotional response scale was used as a means for data collection, and the validity and reliability coefficients were made for this scale. The simple correlation coefficient was used to treat the data statistically.